2009
DOI: 10.1177/1941738109334215
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training in Children and Adolescents: Raising the Bar for Young Athletes?

Abstract: Context:Strength training in children, in combination with plyometric and/or agility training, has become an increasingly popular tactic for athletes to gain a competitive edge during the off-season. The present review clarifies some common myths associated with strength training in children, and it outlines the most current recommendations.Evidence Acquisition:Relevant studies on strength training in children and adolescents were reviewed (search results included studies indexed in PubMed and MEDLINE from 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 41 publications
(71 reference statements)
5
47
1
5
Order By: Relevance
“…Previous literature reports that children can increase muscle strength by 30 to 50% after 8 to 12 weeks of well-designed traditional resistance training (Dahab & McCambridge 2009). Our results demonstrate that calisthenics-based strength training has reached the expectation (↑55.1% for PU and ↑38.9% for CU).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous literature reports that children can increase muscle strength by 30 to 50% after 8 to 12 weeks of well-designed traditional resistance training (Dahab & McCambridge 2009). Our results demonstrate that calisthenics-based strength training has reached the expectation (↑55.1% for PU and ↑38.9% for CU).…”
Section: Discussionsupporting
confidence: 63%
“…Several investigations have demonstrated that strength gains induced by training are possible in this population, mainly due to neuromuscular adaptation (Dahab & McCambridge 2009;Myers et al 2017), and improved intra-and intermuscular coordination. Increased strength may lead to better sport performance and injury prevention (Faigenbaum et al 2013;Faigenbaum & Myer 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the intensity and duration of PA was insufficient to produce change in the outcomes assessed. In addition, given the evidence that long-term involvement in PA may be needed to affect health (ie, fatigue, strength) and QOL outcomes [64-66], the interventions may not have been long enough to affect the studied outcomes. Accordingly, it is possible that increasing the dose of PA, and offering interventions lasting longer, may yield statistically and clinically significant effects on health and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Das Training bei Kindern hängt von vielen Faktoren ab. Menschen, die in der Kindheit regelmäßige Bewegungsgewohnheiten erlernen, setzen dieses idealerweise bis ins Erwachsenenalter fort [21]. Das Training sollte das Ziel haben, die Motivation anzuregen und Einstellungen auszubilden, die zu einem langfristigen Engagement in den Bereichen Sport, Spiel und Bewegung führt [22].…”
Section: Training Und Krafttraining Bei Kindernunclassified
“…Aus biologischer Sicht kann Krafttraining bei Kindern nicht nur die Kraft, sondern auch ihre Knochendichte, Balance, fettfreie Masse und Selbstwertgefühl verbessern [21]. Kinder legen nicht primär durch eine Hypertrophie der Muskulatur, sondern anfangs eher durch eine neuronale Anpassung an Kraft zu [24].…”
Section: Training Und Krafttraining Bei Kindernunclassified